The quality of function of renal allografts is associated with donor age - Higgins, R. M.; Sheriff, M.H.R.; Bittar, A. A.; Richardson, A. J.; Ratcliffe, P. J.; Gray, D. W. R.; Morris, P. J. (John Wiley & Sons, 1995)
The quality of renal allograft function was assessed by prospective measurement of creatinine clearance at 1 year (n = 197) and at 3 years (n = 115) after cadaveric renal transplantation in a cohort of 268 patients treated with triple therapy immunosuppression. Donor age (P < 0.0012) and recipient age (P < 0.01) were independently associated with creatinine clearance both at 1 and at 3 years. In patients with donor age above 50 years and recipient age above 45 years, the mean creatinine clearance was 32.7 (SD 10.4) ml/min (n = 27). When the donor age was below 30 years and recipient age below 45 years, the mean creatinine clearance was 55.6 (SD 14.4) ml/min (n = 47, P < 0.001). However, in these patients there was no significant association between graft function and many of the factors known to influence graft survival, such as HLA matching, sensitisation of the recipient, and the occurrence of rejection. In conclusion, the quality of renal allograft function declined with increasing donor and recipient age in our patients, whilst immunological factors were not significantly associated with function in surviving grafts
Transplant International: 1995; Vol: 8(3); 221-5p.
Keywords: Donor age; renal function - Kidney function; donor age . Age donor; renal function